Two unique cases of Bouveret syndrome with review of literature. Issue 8 (21st August 2022) - Dixon, Austin; Williams, Michael D; Makiewicz, Kristine; Khokar, Amna; Bonomo, Steven
Abstract: Bouveret syndrome is a rare form of gallstone ileus in which a proximally lodged gallstone in the duodenum causes a gastric outlet obstruction. It is a rare condition that can be challenging to manage. Although endoscopic management remains first line, a surgical approach can be needed. We present two cases of Bouveret syndrome. A 65-year-old man with oral squamous cell carcinoma treated with endoscopic management and a 63-year-old woman treated with surgery.